Long-term effects of early overfeeding and food restriction during puberty on cardiac remodeling in adult rats. (11th October 2020) - Chavaglia Cavalet, Letícia; dos Santos Ribeiro, Larissa Cristina; Rosa, Gustavo Bergoli; Sousa, Kássia Kristina; de Melo, Aryanne Batista Soares; Campos, Dhiógenes Balsanufo Taveira; Ferreira, Lucas Araújo; Amaral, Nathalia Oda; Calisto, Yasmin Teixeira Viana; de Castro, Alessandra Gisele; de Castro, Carlos Henrique; Pedrino, Gustavo Rodrigues; et al.
Abstract: Nutritional disorders during the perinatal period cause cardiometabolic dysfunction, which is observable in the early overfeeding (EO) experimental model. Therefore, severe caloric restriction has the potential of affecting homeostasis through the same epigenetic mechanisms, and its effects need elucidation. This work aims to determine the impact of food restriction (FR) during puberty in early overfed obese and non-obese animals in adult life. Three days after delivery (PN3), Wistar rats were separated into two groups: normal litter (NL; 9 pups) and small litter (SL; 3 pups). At PN30, some offspring were subjected to FR (50%) until PN60, or maintained with free access to standard chow. NL and SL animals submitted to food restriction (NLFR and SLFR groups) were kept in recovery with free access to standard chow from PN60 until PN120. Body weight and food intake were monitored throughout the experimental period. At PN120 cardiovascular parameters were analyzed and the animals were euthanized for sample collection. SLNF and SLFR offspring were overweight and had increased adiposity. Differences in blood pressure were observed only between obese and non-obese animals. Obese and FR animals have cardiac remodeling showing cardiomyocyte hypertrophy and the presence of interstitial and perivascular fibrosis. FR animals also show increased expression of AT1 and AT2 receptors and of total ERK and p-ERK. The present study showed that EO leads to the obese phenotype and cardiovascular disruptions. Interestingly, we demonstrated that severe FR during puberty leads to cardiac remodeling.